Explanation of Al-Jami Al-Saghir by Noah bin Mustafa Al-Hanafi (d. 1070 AH) from Plate 60 to Plate 64 - study and investigation - (Islamic Sciences Journal, 2023)
Preoccupation with legal sciences is one of the best acts of worship with Allah Almighty for those whose intentions are righteous, and the most important of them after the sciences of the Noble Qur’an is caring for the purified Prophet’s Sunnah and its sciences. It is part of the mercy of Allah Almighty for this nation that He sent among them a Messenger who teaches them the matters of their religion, and guides them to everything that will benefit them. And he warns them of everything that harms them, and Allah Almighty has equipped men to preserve the Sunnah of the Prophet who believed what they promised Allah, so they preserved it, and their efforts had an impact that is not hidden until it reached us in its form that was during the era of the Messenger of God (peace be upon him). Peace be upon him).The most difficult thing in realizing the manuscript is the task of preserving this historical legacy, preserving it, and displaying it as the compiler wanted, and also not finding some of the sources that the compiler relied on in the manuscript.
Keywords: Explanation, collector, investigation, manuscript, painting.